Spinal cord tumor presenting with neck stiffness - Anood Alassaf (14778064) (2021)
Three years old boy presented with recurrent severe abdominal pain. He was treated for constipation and the pain resolved. Later he developed a limitation of neck movements. Investigations revealed a spinal cord mass. After surgical resection, histopathology confirmed pilocytic astrocytoma. The authors urge clinicians to observe for early signs of spinal cord tumor in children presenting with unusual presentations such as abdominal pain. Early recognition of spinal cord tumors and immediate treatment will prevent life‐threatening complications and improve the prognosis. Other Information Published in: Journal of Pediatric Surgery Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.epsc.2021.102071